FRI0153 Comparisons of work productivity and patient-reported outcomes through 78 weeks among optima study arms 2, 4, and 5. (23rd January 2014) - Kavanaugh, A.F.; Emery, P.; van Vollenhoven, R.; Cifaldi, M.A.; Shaw, J.W.; Chen, N.; Smolen, J.S.
Abstract : Background: Little is known about differences in work productivity (WP) and patient-reported outcomes (PROs) between rheumatoid arthritis (RA) patients (pts) maintained on adalimumab (ADA) and methotrexate (MTX) after achieving low disease activity (LDA) and those initiated on ADA after failing to achieve LDA with MTX alone. Objectives: Using data from the O ptimal P rotocol for T reatment Initiation with M TX and A DA (OPTIMA) study, to assess differences in WP and PROs among pts maintained on treatment after achieving LDA with ADA+MTX or PBO+MTX or who add ADA after failing to achieve LDA with PBO+MTX. Methods: Adults with RA <1 year and active disease were randomized to ADA+MTX ( N =515) or PBO+MTX ( N =517) for 26 weeks (wks). Pts with stable LDA (DAS28CRP <3.2 at wks 22 and 26) on ADA+MTX were re-randomized to ADA+MTX (Arm 2, N =105) or PBO+MTX for 52 wks. Pts with LDA following 26 wks of PBO+MTX continued treatment for another 52 wks (Arm 4, N =112), whilst those without LDA received open-label (OL) ADA+MTX for the same duration (Arm 5, N =348). Pts completed the WP and Activity Impairment (WPAI) questionnaire, Health Assessment Questionnaire Disability Index (HAQ-DI), and Patient Acceptable Symptom State (PASS) classifier at wk 0 (baseline) and subsequent time points. Outcome differences were estimated after imputing missing data. Results: At wk 0, Arm 2 pts had less impairment than pts in Arm 5 (Table ). Arm 2 pts improved between wks 0 and 26 and maintained gains until wk 78 (end of study). Conversely, Arm 4 pts had worsened PASS responses at wk 36 (wk 36-wk 26: -8.1%, p=0.047) and wk 66 (wk 66-wk 26: -13.4%, p=0.003) and a worsened HAQ-DI score at wk 78 (wk 78-wk 26: .1, P=0.041). Compared to Arm 5 pts, pts in Arm 2 exhibited greater improvements in all outcomes at wk 26 and in WPAI Overall Work Impairment (WPAI-OWI) and HAQ-DI scores at subsequent time points. Compared to Arm 4 pts, pts in Arm 2 exhibited a greater improvement in WPAI-OWI score at wk 78 (wk 78-wk 0: -40.6% vs. -27.9%, p=0.045) and greater improvements in PASS response at wk 66 (wk 66-wk 0: 69.3% vs. 47.6%, p=0.009) and wk 78 (wk 78-wk 0: 69.3% vs. 53.8%, p=0.043). Conclusions: Pts continuing on ADA+MTX after achieving LDA maintain WP and PRO gains, whilst pts continuing on PBO+MTX after achieving LDA experience decrements in some PROs. Pts switched from PBO+MTX to OL ADA+MTX due to not achieving LDA exhibit improved outcomes though not to the same degree as ADA+MTX responders who maintain treatment. Disclosure of Interest: A. Kavanaugh Grant/Research support from: Abbott, Consultant for: Abbott, P. Emery Consultant for: Abbott, R. van Vollenhoven Grant/Research support from: Abbott, Consultant for: Abbott, M. Cifaldi Shareholder of: Abbott, Employee of: Abbott, J. Shaw Shareholder of: Abbott, Employee of: Abbott, N. Chen Shareholder of: Abbott, Employee of: Abbott, J. Smolen Grant/Research support from: Abbott, Consultant for: Abbott